Correspondence on Letter regarding “Impacts of muscle mass dynamics on prognosis of outpatients with cirrhosis” - Kim, Tae Hyung; Jung, Young Kul; Yim, Hyung Joon (Clinical and molecular hepatology, 2023)
In our study, change in muscle mass (ΔSMI)/yr%, which represented the change in muscle mass, was not an absolute value but a rate value divided by the muscle mass at inclusion. [...]of sex, the impact of ΔSMI/yr% could be consistent. [...]abstinence is a fundamental treatment with long-term benefits, including a 10–30% reduction in mortality [4,7,8]. [...]drinking behavior after inclusion could be an important factor in the prognosis of patients with cirrhosis, as mentioned by Song et al. [...]as mentioned in the limitations of the original paper, the protocol in our cohort did not include measurements for these factors. [...]studies are required to address these factors.